2017
DOI: 10.1016/j.nicl.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

APPswe/PS1dE9 mice with cortical amyloid pathology show a reduced NAA/Cr ratio without apparent brain atrophy: A MRS and MRI study

Abstract: Transgenic animal models of Aβ pathology provide mechanistic insight into some aspects of Alzheimer disease (AD) pathology related to Aβ accumulation. Quantitative neuroimaging is a possible aid to improve translation of mechanistic findings in transgenic models to human end phenotypes of brain morphology or function. Therefore, we combined MRI-based morphometry, MRS-based NAA-assessment and quantitative histology of neurons and amyloid plaque load in the APPswe/PS1dE9 mouse model to determine the interrelatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(58 reference statements)
1
15
0
Order By: Relevance
“…NAA, as a representative metabolite of neuronal integrity, is found to be reduced in AD, indicating neuronal malfunction either due to diminished neuronal density, neuronal cell loss, or partially reversible neuronal dysfunction [ 45 ], and correlates with disease progression [ 46 ]. Further, APP/PS1 mice also show significantly decreased NAA to Cr ratio [ 28 , 45 , 47 ], which was also observed in the present study. Upon long-term CR, NAA/Cr ratios were increased, reaching the same values as those found in wt mice, indicating improved neuronal integrity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…NAA, as a representative metabolite of neuronal integrity, is found to be reduced in AD, indicating neuronal malfunction either due to diminished neuronal density, neuronal cell loss, or partially reversible neuronal dysfunction [ 45 ], and correlates with disease progression [ 46 ]. Further, APP/PS1 mice also show significantly decreased NAA to Cr ratio [ 28 , 45 , 47 ], which was also observed in the present study. Upon long-term CR, NAA/Cr ratios were increased, reaching the same values as those found in wt mice, indicating improved neuronal integrity.…”
Section: Discussionsupporting
confidence: 89%
“…Brain tissue was fixed in 4% phosphate-buffered formalin, embedded in paraffin and sliced in 4 µm-thin sections. The sections were put on X-tra Adhesive Precleaned Micro Slides (Leica, Wetzlar, Germany) and exposed to mouse monoclonal anti-Aβ antibody (clone 6E10; 1:1000, BioLegend, San Diego, CA, USA, as described by the authors of [ 28 ]) and goat polyclonal anti-iba1 antibody (1:1000, Abcam, Berlin, Germany). DAB chromogen Universal LSAB ® kits (System-HRP; DakoCytomation, Dako, Jena, Germany) were used for development according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Mitolo et al (2019) found that a combination of the ratio of NAA/myoinositol (ml) and the volume of parahippocampal gyrus could improve the overall accuracy of predicting the conversion to AD 2 years before the occurrence of clinical symptoms. The study by Kuhla et al (2017) has shown that based on the MRI morphology and MRS-based NAA evaluation, APPswe/PS1dE9 mice showed an increase in Aβ plaques, a loss of neurons, and an impairment of the NAA/Cr ratio, but no brain atrophy. It was found that the change of NAA as a functional marker rather than the change in volume was more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…MRS spectrum was derived from voxel of interest and was visualized via jMRUI. As previously described by Kuhla et al [30], spectra were analyzed with the spectroscopy package. Metabolite ratios were calculated based on the area under the corresponding fitted curves for N-Acetylaspartate (NAA 2.0 ppm) and creatine (Cr 3.0 ppm).…”
Section: Mr Spectroscopymentioning
confidence: 99%